HAK MEWARIS ANAK ANGKAT TERHADAP HARTA ORANG TUA ANGKAT MENURUT HUKUM PERDATA - Manik Prayustini, Ni Wayan; Rai Setiabudhi, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
Adopted children are often poorly protected, especially when the adoptive parents died, where a foster child who was supposed to have a legitimate position as a child in the foster parents marriage led to neglect of their rights, including the right of next of kin. Therefore it is necessary to know how the procedure of adoption is valid under the Act and how the rights of a child adopted heir on properties adoptive parents according to civil law. This type of research used in this paper is a type of research that is based on the normative juridical rules of law that has to do with the issues raised yag author. Legal adoption procedures in Indonesia is regulated in some legislation, such as : 1917, State Gazette No. 129, the Supreme Court Circular 6 of 1983, Law No. 23 of 2002 on Child Protection, and Government Regulation No. 54 Year 2007 on the Implementation of Child Adoption. Adopted children have the same position with the heirs ab intestato. So should an adopted child has the same status as heir ab intestato to obtain inheritance according to civil law. However 1917, State Gazette No. 129, this gives another restriction of the rights of the adopted child inherits is that the adopted child just become heirs of the parts that are not in a will.
Keywords: Heir Rights , Child Lift , Procedures , Civil Law